Método de estimação da velocidade em motores de indução trifásicos através da corrente de armadura com aplicação da Teoria do Caos - Silva, Marlio Antonio da (2021)
Three-phase induction motors are equipment widely used in the current industrial sector, this fact is explained by their low cost, their robustness, as well as their high operating efficiency. This equipment is present in practically all industrial sectors, which, in turn, makes these machines responsible for a significant portion of the total electrical energy consumed. As a result, it is necessary for three-phase induction motors to operate efficiently, meeting the demand for parameters such as torque and speed suitable for each application. In order to achieve this objective, it is essential to apply efficient control systems, which, through specific algorithms, are able to accurately estimate the rotation speed and adequate response time, which has driven several researches in the area. The present work proposes for the first time the application of the density of maxima chaotic variable for speed estimation in three-phase induction motor shafts. The estimation is performed from the acquisition and processing of electrical current signals from the motor supply in the time domain, without the use of invasive sensors to its structure. The technique presents a lower computational effort than the state-of-the-art techniques and a higher response time than the classical techniques based on the Fourier Transform, allowing the estimation of the speed even with the motor under variable load. Preliminary results show that the method is feasible for this type of application and can be a relevant tool in future frequency inverter projects.